A long‐term study of bottlenose dolphins (Tursiops aduncus) in an Australian industrial estuary: Increased sightings associated with environmental improvements. Issue 1 (24th October 2016) - Bossley, Mike I.; Steiner, Aude; Rankin, Robert W.; Bejder, Lars
Abstract: Delphinids are long‐lived, have delayed maturity and low reproductive rates which necessitate long‐term monitoring programs to detect changes in abundance. Between 1990 and 2013, an observational study of bottlenose dolphins ( Tursiops aduncus ) was conducted in the Port River estuary (Adelaide, Australia). The estuary has received pollution from industry, sewage plants and storm water. In recent years, pollution entering the system has reduced and the establishment of the Adelaide Dolphin Sanctuary (ADS) increased dolphin protection from harassment and deliberate attacks. Nevertheless, the estuary remains a busy port. Over a 24 yr period, we conducted boat‐based surveys ( n = 735) for dolphin groups ( n = 3, 634) along a predetermined route in the Inner and Outer Estuary of Adelaide's Port River estuary. It is our conjecture that major infrastructure changes and pollution abatement have yielded a more favorable marine environment for dolphins, resulting in an estimated 6% annual increase in sightings, from a near absence of sightings in the 1980s. Increased dolphin numbers were likely the result of improved water quality, augmented by surveillance and education arising from the proclamation of the ADS. This study highlights the importance of long‐term monitoring and has implications for dolphin conservation in heavily impacted urban areas and their protection via protected areas.